KEBERTAHANAN PEREMPUAN SIMALANGGANG MENJADI SINGLE MOTHER - Nofrianti Putri Utami; Silfia Hanani (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to determine and analyze the survival of women into a single mother. This was a qualitative research type. Single mothers are respondents in this study. Interview and observation carried out in data collection. The results showed that the task of women becomes more difficult if they become single parents. A woman should have a dual role in her family as a mother and father to her children. Mother is looking for a living for her family and their daily needs. It is concluded that a single mother at the same time must be able to overcome economic, psychological, and social problems in the society environment.